PENERAPAN MODEL PEMBELAJARAN COLLABORATIVE PROBLEM POSING (CPP) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI KALOR KELAS XI SMA - Triyanti, Rita; Z, Fakhruddin; Azhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low cognitive learning outcomes of students in physics, especially on heat material, caused by teacher-centered learning and the lack of active student involvement in the learning process. This study aimed to determine the effect of the Collaborative Problem Posing (CPP) learning model on students’ cognitive learning outcomes in heat material for grade XI senior high school students. This research employed a quasi-experimental method with a posttest only non-equivalent control group design. The sample consisted of 35 students in the experimental class and 36 students in the control class at SMA Negeri 17 Pekanbaru. The research instrument was a cognitive learning outcomes test on heat material. Data were analyzed using normality, homogeneity, and independent sample t-test with SPSS 26. The results showed that the average cognitive learning outcome score of the experimental class was 87.43, while the control class was 78.33. Hypothesis testing obtained a significance value of 0.000 < 0.05, indicating a significant difference between both classes. Therefore, the Collaborative Problem Posing (CPP) learning model had a positive effect on students’ cognitive learning outcomes in heat material.